Modulating the Gameplay Challenge Through Simple Visual Computing Elements: A Cube Puzzle Case Study - Ribelles, Jose; Lopez, Angeles; Traver, V. Javier (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2023)
Positive player’s experiences greatly rely on a balanced gameplay where the game difficulty is related to player’s skill. Towards this goal, the gameplay can be modulated to make it easier or harder. In this work, a modulating mechanism based on visual computing is explored. The main hypothesis is that simple visual modifications of some elements in the game can have a significant impact on the game experience. This concept, which is essentially unexplored in the literature, has been experimentally tested with a web-based cube puzzle game where participants played either the original game or the visually modified game. The analysis is based on players’ behavior, performance, and replies to a questionnaire upon game completion. The results provide evidence on the effectiveness of visual computing on gameplay modulation. We believe the findings are relevant to game researchers and developers because they highlight how a core gameplay can be easily modified with relatively simple ingredients, at least for some game genres. Interestingly, the insights gained from this study also open the door to automate the game adaptation based on observed player’s interaction.
Keywords: games; gameplay modulation; user experience; visualization; IJIMAI